Prevalence of genetic diseases in Holstein crossbred (Frieswal) bulls in India - ALYETHODI, RAFEEQUE R; ALEX, RANI; DEB, RAJIB; KUMAR, SUSHIL; SINGH, UMESH; SHARMA, SHEETAL; SENGAR, GYANENDRA; TYAGI, S; PRAKASH, B (The Indian Journal of Animal Sciences, 2016)
The present study was conducted to assess the prevalence of genetic diseases, viz. BLAD, DUMPS, BC and FXID in Frieswal (Sahiwal × HF) young bulls. We used the standard PCR-RFLP method to genotype animals for BLAD, DUMPS and BC while simple PCR was done to genotype FXID. The identified BLAD carriers were further verified by sequencing. A carrier prevalence of 4.6 % was noticed for BLAD in Frieswal young bulls while no carriers were identified for other genetic diseases. Pedigree analysis revealed that imported semen of Holstein Friesian bull Valeriant may be the source for the spread the BLAD in Indian Frieswal herd. The present study indicates the existence of BLAD carrier animals in Frieswal bull calves eventhough at a relatively low frequency. Hence it is recommended to screen young bulls at early stages for these defective genes in order to avoid spread within the population.